ESTIMATION OF THE IMPACT OF SOME VARIABLES OF AGRICULTURAL ECONOMIC POLICY ON THE IRAQI DOMESTIC AGRICULTURAL PRODUCT FOR THE PERIOD 1994-2015 USING THE METHOD OF COINTEGRATION AND THE ARDL MODEL - & Alhiyali, Muhammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The calculations of gross domestic product (GDP) show the contribution of each sector, whether Service fully or productively, to the formation of the national income.The agricultural sector is an important sector, although it did not take the lead in the composition of GDP because of the large contribution of the oil sector, especially in recent years, which witnessed the return of Iraq to the international oil market. The research aimed to measure the impact of some economic variables in agricultural GDP and analyze the role that these variables can play on the growth of this output, which can promote growth in the Iraqi agricultural sector. The research was based on the quantitative method to arrive at its results by following one of the modern methods to study the causal relationship, the method of multivariate cointegration, the ARDL model and the test of the causal relationship to determine the direction of the relationship between the economic variables studied, based on the assumptions of the economic theory. The study found that there is a long-term effect between the agricultural GDP index and the other economic variables under study and that there is a causal relationship between the long term and the short term.